Assessing the Impact of Innovation Processes on Electronic Systems Technology Adoption - Ouheda, Salem; Murray, Peter A.; Alam, Khorshed; Ali, Omar (Ital Publication, 2024)
Objectives: This study aims to explore the adoption of electronic health records (EHRs) in the Australian private healthcare sector by integrating three prominent innovation models, namely the Technology Acceptance Model (TAM), the Diffusion of Innovation (DOI) model, and the Technology-Organization-Environment (TOE) framework. The objective of the study is to understand how these combined models might better inform the EHR adoption process and identify the key factors influencing successful implementation. Methods/Analysis: An exploratory qualitative research design employing a phenomenological approach was utilized to investigate the research. Data were collected through semi-structured interviews with senior managers at a private hospital in South-East Queensland. Purposive sampling was employed to select participants, ensuring representation from key decision-makers involved in the EHRs planning process. Thematic analysis, guided by the reflexive thematic analysis (RTA) approach of Braun and Clarke, was used to analyze the data and derive insights into the factors influencing EHRs adoption. Findings: Key findings indicate that perceived usefulness and job relevance (from TAM), innovation attributes and communication channels (from DOI), and technological, organizational, and environmental contexts (from TOE) are critical elements for successful EHRs implementation. The study also highlights the importance of user engagement, comprehensive training, leadership support, and financial resources. Novelty/Improvement: This study offers a novel contribution by integrating the TAM, DOI, and TOE models to provide a more holistic understanding of EHRs adoption in the private healthcare sector. It also introduces the concept of time as a critical innovation artefact, highlighting its significance in the adoption process. Doi: 10.28991/ESJ-2024-08-05-02 Full Text: PDF